Efficacy of Bisanar Preparation against Bee Colonies Infested with Varroa Mites - Shodmonov, A. Sh.; Nasimov, Sh. N.; Azimova, D. I.; Babamuratova, N. B.; Egamberganov, Z. B. (American Journal of Biodiversity, 2025)
This article presents the experimental results on the efficacy of the Bisanar preparation in treating bee colonies infested with varroa mites. In our experiments on combating parasitic diseases in bees, three groups were formed. The Bisanar preparation was administered, and it was characterized by increased vitality in the bees, enhanced longevity of worker bees, and the development of immunity against various types of diseases.